2010
DOI: 10.1097/ta.0b013e3181d865c0
|View full text |Cite
|
Sign up to set email alerts
|

Damage Control Techniques for Common and External Iliac Artery Injuries: Have Temporary Intravascular Shunts Replaced the Need for Ligation?

Abstract: TIVSs have replaced ligation as the primary damage control procedure for injuries to common and external iliac arteries. As a result, the high incidence of subsequent amputation has been virtually eliminated. With increased TIVS experience, an improvement in survival is likely.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 35 publications
(88 reference statements)
1
26
0
1
Order By: Relevance
“…Specifically, Feliciano and colleagues from Grady demonstrated that early restoration of flow with shunts followed by revascularization was associated not only with improved limb salvage but a near doubling of survival when compared with iliac injury ligation. 22 Findings from the current study confirm and extend these publications and facilitate assessment of the efficacy of shunts on functional recovery as well as identification of conditions in which their use may be most advantageous.…”
Section: Discussionsupporting
confidence: 86%
“…Specifically, Feliciano and colleagues from Grady demonstrated that early restoration of flow with shunts followed by revascularization was associated not only with improved limb salvage but a near doubling of survival when compared with iliac injury ligation. 22 Findings from the current study confirm and extend these publications and facilitate assessment of the efficacy of shunts on functional recovery as well as identification of conditions in which their use may be most advantageous.…”
Section: Discussionsupporting
confidence: 86%
“…Although the understanding of TIVS use for military and civilian settings is increasing [42], the optimal shunt material, dwell time, and anticoagulation requirements remain poorly studied; it is clear, however, that TIVS are remarkably durable and rarely clot unless they are too small (diameter), kink because of inappropriate length, and/or are placed in an extremity without appropriate (or shunted) venous outflow (venous hypertension leads to arterial thrombosis) [43]. Although the literature is scattered with case series using TIVS, the most dramatic example of their utility surrounds the near complete disappearance of limb loss following ligation of the common and/or external iliac arteries [43]. More specifically, despite similar injury and patient characteristics, the improvement in amputation rate from 47 to 0% in 22 patients with the introduction of TIVS at a high-volume penetrating trauma center is remarkable [43].…”
Section: Vascular Damage Control Surgical Techniquesmentioning
confidence: 99%
“…Current indications for TIVS include: replantation, open extremity fractures with concurrent extensive soft tissue loss and arterial injury (Gustilo IIIC), peripheral vascular damage control, truncal vascular damage control, and temporary stabilization prior to transport [37,43]. Although the understanding of TIVS use for military and civilian settings is increasing [42], the optimal shunt material, dwell time, and anticoagulation requirements remain poorly studied; it is clear, however, that TIVS are remarkably durable and rarely clot unless they are too small (diameter), kink because of inappropriate length, and/or are placed in an extremity without appropriate (or shunted) venous outflow (venous hypertension leads to arterial thrombosis) [43].…”
Section: Vascular Damage Control Surgical Techniquesmentioning
confidence: 99%
“…In a 2005 report from Feliciano at Grady Memorial, the use of temporary vascular shunts to manage iliac artery injuries resulted in a dramatic decrease in rates of amputation (47% to 0%) and death (73% to 43%). 41 Mesenteric arterial injuries are rare but have high associated mortality. Again, strategies are historically limited to the decision of whether to repair or ligate the injury.…”
Section: Truncal Vascular Injuriesmentioning
confidence: 99%